Thực trạng quản lí hoạt động giáo dục đạo đức cho học sinh thông qua hoạt động trải nghiệm, hướng nghiệp ở một số trường trung học cơ sở tại thành phố Hà Nội - Nguyễn, Thị Thi (Tạp chí Giáo dục, 2025)
Moral education is an integral part of comprehensive education content to help the young generation form ideals, moral consciousness and sentiments, creating ethical behaviors and habits of new socialist people. In the current period, moral education activities for students through experiential activities and career guidance in junior high schools in Chuong My district, Hanoi city in recent years have been valued and achieved certain results, contributing significantly to the goal of comprehensive education for students. The study surveyed 32 managers and 120 teachers of 6 junior high schools in Hanoi city on the current status of moral education management for students through experiential activities and career guidance. The survey results will be the basis for educational managers to have appropriate management measures, contributing to creating positive changes in personality development and moral education for students.